2012
DOI: 10.1080/17535069.2012.656455
|View full text |Cite
|
Sign up to set email alerts
|

How do people vote in suburbia? Political preference and suburbanisation in Europe

Abstract: An important aspect of understanding the urban fringe is to know the political preferences of its inhabitants, since geographically bound political patterns have consequences for both local policymaking and the national political sphere. Combining urban geography approaches that explain the interaction between spaces and society with political science theory on (geographical) cleavages, this article explains differences in electoral preferences between core city and suburban voters. The analyses show how voter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…By the late 1960s, possible differences were beginning to manifest, and initial studies undertaken in the United Kingdom (Cox, 1968) and the United States (Biel, 1972, Gainsborough, 2005 confirmed the need to differentiate between urban, suburban and rural citizens. More recently, De Maesschalck (2011a; 2011b) has replicated these results for Belgium, while Strobele (2012) found further evidence of urban-suburban differences in a crossnational study of France, Germany, the Netherlands, and Switzerland. Given the cross-national findings, the relevance of this potential political cleavage in the Canadian context seems apparent.…”
mentioning
confidence: 82%
“…By the late 1960s, possible differences were beginning to manifest, and initial studies undertaken in the United Kingdom (Cox, 1968) and the United States (Biel, 1972, Gainsborough, 2005 confirmed the need to differentiate between urban, suburban and rural citizens. More recently, De Maesschalck (2011a; 2011b) has replicated these results for Belgium, while Strobele (2012) found further evidence of urban-suburban differences in a crossnational study of France, Germany, the Netherlands, and Switzerland. Given the cross-national findings, the relevance of this potential political cleavage in the Canadian context seems apparent.…”
mentioning
confidence: 82%
“…Studies in the United Kingdom have shown that London suburbanites prefer the Conservative Party over other political parties (Biel, 1972;Cox, 1967;Johnston, Jones, Sarker, Propper, & Bolster, 2004); research finds that Australian suburban areas are more likely to vote for conservative parties (Duncan & Epps, 1992;Johnston & Forrest, 1985);De MaesschalckMaesschalck (2009 finds that suburban areas in Belgium generally vote for more conservative parties and are more likely to display antiforeigner attitudes than inner city areas; and Ströbele (2012) shows that, in most cases, suburbanites in Switzerland, Germany, Holland, and France are more likely to vote for conservative parties and more likely to hold traditional views about women's role in raising children.…”
Section: Residential Zone Values and Policy Preferencesmentioning
confidence: 97%
“…The salience of the rural–urban divide in Switzerland is also reflected in a recent report that surveys feelings of resentment and finds that rural residents hold higher levels of resentment about their political, economic and societal position than their urban counterparts (Hermann et al., 2023). Despite this salience of the Swiss rural–urban divide, most studies to date focus either on direct democratic votes or elections (Kübler et al., 2013; Ladner, 2004; Linder, 2015; Linder et al., 2008; Mantegazzi, 2021), or the role of the suburbs as a third category (Kübler, 2022; Kübler & Bijl‐Schwab, 2014; Longchamp, 2015; Scheuss, 2013; Ströbele, 2012, 2017). However, no research known to me looks into other aspects of the Swiss rural–urban divide, such as political trust.…”
Section: Theoretical Considerationsmentioning
confidence: 99%